Extending the Technology Acceptance Model (TAM) to Predict Student Learning Outcomes in GNS3 Based Networking Education - Masna, Ummul Khaeri; Salim, Agus; Ramadani, Fitra; Baso, Fadhlirrahman (Information Technology Education Journal, 2026)
Purpose – This study investigates the factors influencing network simulator acceptance and its direct impact on learning outcomes within the Department of Informatics and Computer Engineering. It addresses the gap between technology adoption and actual academic success in a technical vocational context. Design/methods/approach – A quantitative approach using the Technology Acceptance Model (TAM) was applied. Data from 187 students were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0, employing a 5,000-resample bootstrapping procedure. Findings – Results confirm that Perceived Usefulness significantly drives Behavioral Intention (β= 0.774, p < 0.001), while Perceived Ease of Use is non-significant (β = 0.150, p = 0.166). Crucially, Behavioral Intention strongly predicts Learning Outcomes (β = 0.849, p < 0.001). The model exhibits substantial predictive power, explaining 83% of the variance in intention (R2 = 0.830) and 72.1% in learning outcomes (R2 = 0.721). Research implications/limitations – Engineering pedagogy should prioritize demonstrating the industrial utility of simulators over interface simplicity. Limitations include the cross-sectional design and reliance on self-reported data within a single department, which may affect generalizability. Originality/value – This research empirically bridges technology acceptance with tangible academic performance in the Indonesian technical education context. It provides a validated framework for enhancing technical competencies through strategic tool integration.